KEANEKARAGAMAN IKAN DI SUNGAI BELUMAI KABUPATEN DELI SERDANG Diversity of fish in Belumai River, Deli Serdang District - M Mahrozi Sagala; Pindi Patana; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
ABSTRACTThis research was conducted in Belumai River, Deli Serdang District in May-June 2014. The aim this research was to measure relative abundance, diversity, evennes and dominance of fish and the relationship with physical and chemical factors of water. The method used “Purposive Random Sampling”. Fisihing gear used gill net, fishnet stocking and fish rod. Data were analyzed descriptive and multiple regression analysis. This research in 8 families, 12 genus, 14 species and 204 individual fishes. Diversity index was 1,18 – 1,91, evennes index 0,73 – 0,86 and dominance index 0,17 – 0,37. Temperature was 28 – 29,75oC, turbidity 3,25 – 14,98 NTU, depth 0,78 – 2,58, flow velocity 0,18 – 0,77 m/sec, pH 5,9 – 7,2 and DO 1,81 – 5,02 mg/l. Regression results showed strong relationship among components. It’s seen from the range of the coefficient determination (R2) 0,866 – 0,900.Keywords: River, Diversity, Fish, Belumai.